2016
DOI: 10.1002/14651858.cd005146.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol plus promethazine for psychosis-induced aggression

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 86 publications
2
43
0
1
Order By: Relevance
“…The major findings of this study are that first-generation antipsychotics like haloperidol or droperidol are administered with adjunctive medications such as benzodiazepines, promethazine, benztropine, or diphenhydramine only 49.5% of the time. Although this study was not designed to investigate the beneficial effects of these combinations, it is notable that there is substantial literature that suggests the idea of doing so, specifically in the case of acute psychosis or undifferentiated agitation (9,(28)(29)(30)(31). In contrast to a 2012 Cochrane review, which suggested that 1 in 5 patients developed acute dystonia after administration of haloperidol alone, a second Cochrane review summarizing trials with haloperidol administered with promethazine found that approximately 1 in 15 patients developed some sort of preventable adverse effect after haloperidol alone (18,28).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The major findings of this study are that first-generation antipsychotics like haloperidol or droperidol are administered with adjunctive medications such as benzodiazepines, promethazine, benztropine, or diphenhydramine only 49.5% of the time. Although this study was not designed to investigate the beneficial effects of these combinations, it is notable that there is substantial literature that suggests the idea of doing so, specifically in the case of acute psychosis or undifferentiated agitation (9,(28)(29)(30)(31). In contrast to a 2012 Cochrane review, which suggested that 1 in 5 patients developed acute dystonia after administration of haloperidol alone, a second Cochrane review summarizing trials with haloperidol administered with promethazine found that approximately 1 in 15 patients developed some sort of preventable adverse effect after haloperidol alone (18,28).…”
Section: Discussionmentioning
confidence: 99%
“…Although this study was not designed to investigate the beneficial effects of these combinations, it is notable that there is substantial literature that suggests the idea of doing so, specifically in the case of acute psychosis or undifferentiated agitation (9,(28)(29)(30)(31). In contrast to a 2012 Cochrane review, which suggested that 1 in 5 patients developed acute dystonia after administration of haloperidol alone, a second Cochrane review summarizing trials with haloperidol administered with promethazine found that approximately 1 in 15 patients developed some sort of preventable adverse effect after haloperidol alone (18,28). This review noted that ''haloperidol used on its own is at such risk of generating preventable adverse effects that unless it is the only choice, this evidence directs that this sole treatment should be avoided'' [(28), p. 2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FGApreparater gitt som injeksjon, medfører stor risiko for akutte nevromuskulaere bivirkninger dersom det ikke samtidig gis antikolinerge antiparkinsonmidler (325). Hos svaert motorisk urolige pasienter brukes noen ganger den motorisk dempende effekten av dopaminblokade for å holde pasienten i ro.…”
Section: Bivirkningunclassified